Responses of autumn staging waterbirds to wetland restoration and water levels in a Danish river delta - Bregnballe, Thomas; Amstrup, Ole; Bak, Mogens (Wildfowl, 2013)
A 2,200 ha wetland in the Danish Skjern River valley was restored between 1999–2002, partly to re-establish a rich community of migratory waterbirds, in a project which aimed to restore the nutrient retention capacity of the area and to improve its overall value for wildlife and humans. Numbers, distribution and foraging activity of waterbirds were monitored over the first four years after restoration, between late August and late November in 2002–2005. The restoration turned the western part of the project area into important feeding and roosting habitat especially for dabbling ducks, but also for herons, swans, coots and waders during their autumn migration. A total of 109 waterbird species were observed inside the restoration area. Dabbling ducks exploited the area extensively, with Wigeon Anas penelope as the most numerous species reaching up to 12,600 individuals. There was no clear increase or decrease in the number of bird-days for geese, swans, dabbling ducks and Coot Fulica atra over the first four years after restoration, except for Gadwall A. strepera and Shoveler A. clypeata which were not numerous in the first autumn. The number of bird-days increased over the study period for three species of diving ducks and decreased for two species of waders. The proportion of dabbling ducks recorded feeding during the day was high in three years (range of annual means for six species = 29–76%) but low in one year (range = 9–44%). Many ducks also flew at dusk to feed in adjacent fields and other wetlands. In shallow lakes numbers of Coot and some species of dabbling ducks decreased with increasing water levels, whereas diving duck numbers increased.